Exozentrische Konstruktionen im Deutschen und Polnischen - Prokop, Izabela (Studia Germanica Posnaniensia, 2018)
Exocentric (aredundant) constructions to which belong e.g. prepositional phrases periphrastic forms within the verb phrase, phraseologisms, idiomatic expressions, are the result of analysis of syntactic constructions according to the method of immediate constituents. The article contains their survey together with the examples of derivation in Polish and German.